Odpowiedzi

2010-03-15T19:17:39+01:00
A) 3x(x-5)-3x(x+7)=72
3x²-15x-3x²-21=72
-15x=93//:-15
x=-6 i 2/10


b) (x-2)^3-3x(2-x)= x^2(x-3)+10
x³-2³-6x-3x²=x³-3x²+10
x³-6x-3x²-x³+3x²=12+10
-6x=22//-6
x=-3,6(...)


c) x/5 +3 = 2/3 + x+1/5
x/5-x=-3+2/3+1/5 / * 15
3x-3x=-15+10+3
0=-2



mam nadzieje ze pomoglam
pozdrawiam.;)
licze na naj.;P
3 4 3
Najlepsza Odpowiedź!
  • kuag
  • Rozwiązujący
2010-03-15T19:39:41+01:00
A) 3x(x-5)-3x(x+7)=72
3x^-15-3x^-21x=72
3x^-3x^-21x=72+15
-21x=87//(podzielić przez)-21
x=-4 i 3/21
w tym przykładzie x^ oznacza x do kwadratu

c) x/5+3=2/3+x+1/5 /razy 15
15 razy x/5+15 razy3=15razy2/3+15x+15razy1/5
3x+45=10+15x+3
3x-15x=13-45
-12x=-32//(podzielić przez)-12
x=2i8/12
x=2i 2/3

b)
(x-2)^3-3x(2-x)=x^2(x-3)+10
x^3-8-6x-3x^2=x^3-3x^2+10
x^3-6x-3x^2-x^3+3x^2=10+8
6x=18//6
x=3
1 5 1